Освітньо-науковий потенціал України в аспекті міжнародного руху людського капіталу - Гуменюк, Ю.П. (Економіка промисловості, 2013)
Розкрито сутність освітньо-наукового потенціалу як конкурентної переваги населення країни на міжнародному ринку праці. В аспекті порівняльного аналізу досліджено рівень освітньо-наукового потенціалу України та доведено необхідність розвитку вітчизняної науки як стратегічного ресурсу структурних змін економіки, які б сприяли трансформації України з ремітера у ремітента висококваліфікованої робочої сили. Раскрывается суть образовательного и научного потенциала, как конкурентное преимущество населения страны на международном рынке труда. С точки зрения сравнительного анализа исследованы уровень образовательного и научного потенциала Украины и доказана необходимость развития науки, как стратегического ресурса структурных изменений в экономике, что способствовало бы превращению Украины из ремитера в ремитента высококвалифицированной рабочей силы. Educational and scientific potential of Ukraine is the result of and a prerequisite for the social-economic development. In 1990 6.5% of global scientific and technical potential were focused in Ukraine; 11 people out of a thousand employed were engaged in scientific and technical sphere. Only in 2006 in the United States the number of researchers per thousand employed reached 6.0 people, in France – 8.3, Germany – 7.2, PRC – 1.6, and Brazil – 1.3, respectively. The purpose of the article is to study the educational and scientific potential of the country and prove the need for the development of science as a strategic resource for structural changes. The liberalization of the international movement of capital in the second half of the twentieth century led to the remove of the legal migration of labour force and expansion of the scope of its illegal migration movement. The countries of the post-Soviet space have lost the status of leading countries of the world, and put dawn to the level of low quality players. Real spending on R & D in Ukraine in 2001 accounted for only 40% of the level of 1991. The pace of falling the spending on R & D in the 1990s, exceeding the pace of falling GDP and reduction of the material bases of research, were faster than the reduction of scientific personnel. However, the research group of scientists from the University of Melbourne showed that in 2011 Ukraine was at the 25th position among 48 countries offering the best higher education in the world. Meanwhile, the shortage of personnel in domestic science and high-tech sector is clearly recognized as the biggest problem of the development of innovative components of the national economy. The author’s research applied to three main reasons of undermining scientific potential: political instability, mass emigration of scientists and lack of interest in scientific growth. So, political instability is manifested in corruption, which is recognized as the biggest challenge for social transformation; the lack of interest is a consequence of the complications of self-realization in terms of corruption that causes undermining the scientific potential of the country and emigration of the workforce of the highest category.